Compositional influence on heating-induced clustered glass formation for multicomponent Zr55-60Al10(Co, Ni, Cu, Ag)30-35 alloys. (August 2021) - Wan, Y.X.; Li, H.S.; Chen, C.J.; Kong, F.L.; Shen, B.L.; Churyumov, A.; Shalaan, E.; Al-Ghmadi, A.A.; Botta, W.J.; Inoue, A.
Abstract: The compositional influence on the formation of a clustered glassy structure was examined for Zr-based metallic glasses with multicomponent compositions of Zr60 Al10 Co30-x (Ni, Cu, Ag)x (x = 5–20, at.%) and Zr55 Al10 Co10 Ni10 Cu10 Ag5 subjected to long-time annealing at the temperatures above the first-stage crystallization peak temperature ( T p1 ). The glassy alloys are characterized as two different groups, namely, (1) the irregular bulk glassy type with positive heat of mixing among the solute elements, and (2) the pseudo-high entropy alloys consisting of one major element and four solute elements or more with equiatomic or nearly equiatomic compositions. As-spun ribbons of the irregular type Zr–Al–Co–Ag glasses with 5 at.% and 10 at.% Ag exhibit two exothermic peaks with a wide temperature interval of 220–240 K. Besides, the glassy phase remains unchanged, as seen in the high-resolution TEM images, even after annealing for 1.8–21.6 ks at the temperatures well above T p1, indicating the formation of the clustered glassy phase. However, no clustered glass is recognized for the other alloys and hence the suitable contents of Co and Ag elements play a dominant role in the formation of the clustered glass. The clustered glassy phase was also formed for Zr60 Al10 Co25 Ag5 and Zr60 Al10 Co20 Ag10 alloy rods of 1.5 mm in diameter. The clustered glasses exhibit much higher Vickers hardness of ~700 exceeding those for the other crystallized alloys. The formation criteria of the clustered glass with higher thermal stability, hardness and glass-forming ability are useful for future synthesis of an elevated-temperature strength metallic glass. Highlights: Multicomponent glassy Zr55 –60 Al10 (Co, Ni, Cu, Ag)30-35 alloys were formed. The high thermal resistance enables the formation of a clustered glassy phase. The Co and Ag elements play a dominant role in the formation of the clustered glass. Vickers hardness increases drastically to >800 for clustered glassy + crystal phases.